Achieving compliance with the World Anti-Doping Code: learning from the implementation of another international agreement. Issue 2 (3rd April 2019) - Gray, Stacie
ABSTRACT: The scale of the compliance problem that the World Anti-Doping Agency (WADA) faces was recently highlighted by the exposure of institutionalised doping in Russia and the series of doping scandals within athletics. The article aims to analyse the problems of achieving compliance with the World Anti-Doping Code. Specifically, the article explores the techniques for, and problems of, achieving compliance with the Code and a similar international agreement. The chosen agreement is the UN Convention Against Transnational Organised Crime, with a specific focus upon anti-money laundering. The anti-doping and anti-money laundering regimes were analysed to identify the range of strategies used to achieve (or at least enhance) the level of compliance with the respective international convention. The anti-money laundering strategies were also evaluated to assess their effectiveness as a way of generating ideas for improving compliance with the WADA Code. To analyse compliance, three inter-related bodies of theory were used: regime theory, implementation theory and compliance system theory. Qualitative document analysis was used to analyse documents published by relevant organisations. Additionally, semi-structured interviews were conducted with senior staff members responsible for monitoring compliance at the international and UK domestic level. The results identified a range of strategies used to achieve compliance, including sanctions, random monitoring mechanisms and whistleblowing. It is concluded that the identified strategies have had modest and variable success in improving compliance, yet have the potential to address the problems of achieving compliance with the 2015 WADA Code.